Plano de ações articuladas na gestão da educação de municípios pertencentes à associação dos municípios da zona da produção (AMZOP) - RS - Cichelero, Silvana Maria Tres (2018)
This Professional Master's Degree Program in Public Policy and Educational Management was developed in the line of Public Policies and Education Management, and refers to Municipal Education Management from the implementation of the Articulated Actions Plan (PAR). The general objective was to analyze the limits and possibilities brought by the Articulated Actions Plan (PAR) for the Education Management of municipalities of the State of Rio Grande do Sul, belonging to AMZOP (Association of Municipalities of the Production Zone), with a view to building a Proposed Continuing Education. The problem was established: what are the limits and possibilities brought by the Joint Action Plan for the Management of Education in the municipalities belonging to the AMZOP (Association of Municipalities of the Production Zone)? The methodological processes were based on the qualitative approach (FLICK, 2009,2012), characterized as a multiple case study (YIN, 2001, TRIVIÑOS, 1987). As data collection instruments, online questionnaires were used through the google docs application, sent to all the Secretariats of Education of the municipalities of AMZOP. For data analysis, data triangulation (GIL, 2008, FLICK, 2009) and content analysis were performed (BARDIN, 2011). For that, the categories of analysis were listed: Municipal Management, Democratic Management and Articulated Actions Plan, and these were divided into subcategories of analysis. Based on bibliographical, documentary and state of knowledge research, and from the data obtained through empirical research, the limits and possibilities that PAR brought to education in the municipalities were listed. The main possibility was the access to financial resources of infrastructure for the educational networks. And the main limitation was the centralization of resources and decisions at the federal level. The study confirms, singular changes in the management of education in the municipalities, from the PAR. There is a need for a more in-depth and critical analysis of the plan and the management that has been developed, regarding the democratization of education in the light of the principles of autonomy, decentralization of power and effective participation of the community in decision-making. Because these principles are not fully incorporated and effective in the educational and school management of AMZOP's municipal education networks. In this sense, as a product of this study, a Proposal for Continuing Education on the Articulated Actions Plan and Educational / Democratic Management was developed, which enables the construction and acquisition of knowledge about Municipal Education Management in a Democratic and participatory perspective and the Plan of Articulated Actions and their unfolding. Seeing ways to incorporate PAR as a methodology for democratic planning and participatory management of municipal education, based on the effective participation of all educational segments in its planning, monitoring and follow-up. Increasing and strengthening spaces and instruments for the democratic management of education systems.